Nonlinear Finite Element Analysis of Beam Structures with and without Openings Using ANSYS: A Comparative Study - Pokhrel, Sarthak; Koirala, Himal (Mid-West University Journal of Engineering & Innovation, 2025)
Beams play a crucial role in numerous structures like buildings, bridges, and aircraft. This research utilizes ANSYS software for nonlinear FEA to investigate the impact of rectangular openings on beam structural behavior under vertical loads. In the research, two beam models are analyzed, one being solid while the other has rectangular openings. Studying the impact of openings on stress concentrations and failure modes is a key objective, as well as evaluating load-carrying capacity, deformation, and stress distribution. The results indicate that solid beams display consistent linear stress distributions, while beams without openings exhibit significant alterations due to localized stress concentrations, leading to more deformation and reduced load-carrying capacity. The findings stress the importance of considering openings in beam design to ensure structural strength and safety. By conducting this study, our goal is to enhance engineering techniques and facilitate the development of robust structural plans that meet safety standards and address practical requirements by exploring the impacts of incorporating openings. Ultimately, this study enhances understanding of beam performance under real-life loading conditions, allowing informed decisions in structural engineering designs.